A numerical study on the influence of solidity on the performance of vertical axis wind turbines - Eboibi, Okeoghene (Philippine Engineering Journal)
Computational Fluid Dynamics has been used to test seven configurations of a 5kW three-bladed Vertical Axis Wind Turbine based on a NACA0012 profile. The turbine aerofoil chord has been changed to alter the turbine solidity and this has been tested over a wide range of tip speed ratios. Validation is based on comparison to tests on a pitching aerofoil, at a similar Reynolds number. The investigations determined how and why the change in aerofoil chord and therefore solidity affected the performance of the turbine. The aerofoil chord lengths investigated varied between 0.098m and 0.48m resulting in solidities of between 0.2 and 0.98. An energy yield analysis method was developed to determine the configuration of the turbine with best performance assuming the configurations operated over a Rayleigh wind distribution with an annual mean value of 6m/s. The results showed that the characteristics of the turbine map (Cp vs. ) for a solidity of 0.3 were most favorable for the given wind distribution and resulted in the highest energy yield.